A new decision making method based on Z-decision-making trial and evaluation laboratory and ordered weighted average and its application in renewable energy source investment - Su, Xiaoyan; Guan, Xuefan; Xu, Zhihui; Qian, Hong (Frontiers in Energy Research, 2022)
Decision-making methods are widely used in renewable energy source (RES) investment. In practical applications, various conditions need to be considered during the decision-making process, such as uncertainty and reliability of information, dependence among criteria, and different risk preferences of the decision makers. However, there is currently a lack of effective consideration of all these conditions. In this article, a new decision-making method based on Z-DEMATEL and the maximal entropy OWA operator is proposed, where Z-number is used to characterize the uncertainty and reliability of the information, decision-making trial and evaluation laboratory (DEMATEL) technique, and the maximal entropy ordered weighted average (OWA) operator are used to deal with dependence and risk preference, respectively. The application example in RES investment and discussions show the effectiveness and the advantages of the proposed method.